PENDAMPINGAN GURU SD DI DAERAH RAWAN BENCANA GUNUNG SINABUNG MELALUI KESIAPSIAGAAN BENCANA DAN BUDIDAYA HIDROPONIK BERBASIS INTERACTIVE FLAT PANEL (IFP) - Laurensia Masri Perangin-angin; Halimatussakdiah; Imelda Free Unita Manurung; Rani Marisanta Br. Simanjuntak (JS (JURNAL SEKOLAH), 2026)
Abstract: The problems identified at SDN 047175 Simacem Bekerah indicate that disaster preparedness has not been systematically integrated into the learning process, teachers’ competence in delivering disaster-related content remains limited, and the utilization of interactive learning technology such as Interactive Flat Panel (IFP) is still suboptimal. This condition is exacerbated by the school’s location in a disaster-prone area of Mount Sinabung and the limited availability of contextual learning resources.To address these issues, a community service program was implemented by integrating disaster preparedness education, hydroponic-based environmental learning, and the use of IFP technology. The implementation method consisted of four stages: preparation, implementation, assessment, and evaluation. The results showed significant improvements in teachers’ knowledge (from approximately 30% to ≥80%), digital skills (≥70% of teachers were able to use IFP effectively), and student engagement in project-based learning (≥75%). In conclusion, this program is effective in enhancing disaster literacy, teachers’ digital competence, and contextual learning practices. It is recommended that the program be sustained and replicated in other disaster-prone schools. Keywords: disaster preparedness, hydroponics, Interactive Flat Panel, elementary school teachers, Mount Sinabung Abstrak: Permasalahan yang ditemukan di SDN 047175 Simacem Bekerah menunjukkan bahwa pembelajaran belum mengintegrasikan kesiapsiagaan bencana secara sistematis, keterampilan guru dalam mengajarkan kebencanaan masih terbatas, serta pemanfaatan teknologi pembelajaran interaktif seperti Interactive Flat Panel (IFP) belum optimal. Kondisi ini diperparah oleh letak geografis wilayah yang berada di kawasan rawan bencana Gunung Sinabung serta keterbatasan sarana pembelajaran kontekstual. Upaya menyelesaikan permasalahan tersebut, dilakukan program pendampingan berbasis integrasi kesiapsiagaan bencana, pembelajaran hidroponik, dan pemanfaatan IFP. Metode pelaksanaan meliputi tahap persiapan, pelaksanaan, penilaian, dan evaluasi. Hasil kegiatan menunjukkan peningkatan signifikan pada pemahaman guru (±30% menjadi ≥80%), keterampilan pemanfaatan teknologi (≥70% guru mampu menggunakan IFP), serta keterlibatan siswa dalam pembelajaran berbasis proyek (≥75%). Kesimpulannya, program ini efektif dalam meningkatkan literasi kebencanaan, keterampilan digital, dan pembelajaran kontekstual berbasis lingkungan. Rekomendasi diarahkan pada keberlanjutan program dan replikasi di sekolah rawan bencana lainnya. Kata kunci: kesiapsiagaan bencana, hidroponik, IFP, guru SD, Sinabung